Serious Fun : the Power of Improvisation for Learning and Life. - Yamamoto, Ruth (Hamilton Books, 2016)
The importance of play and fun to people's lives cannot be stressed enough in today's cultural climate of high stress, high stakes, and competition. One activity that gains recognition and credibility as both fun and transformative is theatrical improvisation or improv. In this book, Ruth Yamamoto reviews her research on the influences of improvisation on community college students.